In pursuit of the rejected "Jew from the Golah”. On life and works of dr. Jacob (Kobi) Weitzner - Lewkowicz-Shenholz , Lior Ester (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2023)
Since the establishment of the state of Israel in 1948 everything related to the Diaspora (“Golah”) such as culture, language, or mentality was considered despicable and Israelis tried to keep away from it. Dr. Jacob (Kobi) Weitzner a writer, playwright and Yiddish theater director. This article is not about his academic achievements or artistic works, but his seminal activity for the preservation of Jewish culture in the Diaspora.